2009
DOI: 10.1093/nar/gkn1055
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Taq DNA polymerase resistant to PCR inhibitors allow DNA amplification from whole blood and crude soil samples

Abstract: Potent PCR inhibitors in blood and soil samples can cause false negative results from PCR-based clinical and forensic tests. We show that the effect of these inhibitors is primarily upon Taq DNA polymerase, since mutational alteration of the polymerase can overcome the inhibition to the extent that no DNA purification is now required. An N-terminal deletion (Klentaq1) is some 10–100-fold inhibition resistant to whole blood compared to full-length, wild-type (w.t.) Taq, which is strongly inhibited by 0.1–1% blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
179
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(187 citation statements)
references
References 49 publications
5
179
1
2
Order By: Relevance
“…by mutations [11]. In the current study, sample type had a notable impact on the performance of the two tested alternative DNA polymerases.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…by mutations [11]. In the current study, sample type had a notable impact on the performance of the two tested alternative DNA polymerases.…”
Section: Discussionmentioning
confidence: 69%
“…However, AmpliTaq Gold might not be the optimal choice for samples containing PCR inhibitors. In several studies, AmpliTaq Gold has shown lower tolerance to PCR-inhibitory substances compared with other DNA polymerases [7][8][9][10][11]. We have previously shown that short tandem repeat (STR) DNA analysis of complex crime scene samples can be improved by replacing AmpliTaq Gold with either of the alternative DNA polymerase-buffer systems Bio-X-Act Short (Bioline, London, UK), ExTaq Hot Start (TaKaRa Bio, Shiga, Japan), or PicoMaxx High Fidelity (Stratagene, La Jolla, CA, USA) [6].…”
Section: Introductionmentioning
confidence: 99%
“…proteases from food particles, bacterial cells) (14) than in blood (e.g. heme, hemoglobin, lactoferin, immunoglobin G) (15,16,17). Saliva transports exfoliated epithelial cells from buccal mucosa which contains DNA and the mean number of epithelial cells per 1 mL of saliva is about 4.3 × 10 5 , which makes it a suitable source of genomic DNA (8,11,18).…”
Section: Sources Of Dnamentioning
confidence: 99%
“…Instead of solid-phase extraction, in the selected example, PCR is directly performed by inactivating the inhibitors in the sample. In addition, an inhibitor-resistant Taq mutant (Kermekchiev et al, 2009) of the Taq polymerase enzyme is used, which minimizes the incubation period. The device was tested with the identification of the 108-bp segment of the DYZ1 region within the human genome, which has application in sex determination (Jobling et al, 1997).…”
Section: Sample Preparationmentioning
confidence: 99%